Enhanced electrochemical performance of flexible polymer supercapacitors through optimization of organic acid-doping, carbon nanomaterials, and fabrication techniques - Parul; Lakshmi, Racherla Bhagya; Utturkar, Vivek; Natu, Varun; Aramanda, Shanmukha Kiran; Ramamurthy, Praveen C.; Kaka, Fiyanshu (Journal of Power Sources, 2026)
The proliferation of portable and wearable electronics necessitates flexible, high-performance energy storage devices. Flexible supercapacitors are poised to meet these demands due to their high power density, flexibility, and durability but scalable fabrication remains challenging due to costly and complex manufacturing methods. This study addresses this issue by implementing scalable, cost-effective spray coating and screen printing techniques to fabricate flexible micro-interdigitated supercapacitors (FMIS) based on Polyaniline (PANI) composites with carbon nanomaterials, using organic acids as crosslinking agents synthesized via hydrogel strategy. The formation of PANI emeraldine salt was verified through X-ray photoelectron spectroscopy, indicating key amine and imine functionalities, while scanning electron microscopy revealed surface morphologies with enhanced active surface areas beneficial for charge storage. Advanced 3D tomography maps porosity distribution and surface area per unit volume, correlating with electroactive areas calculated from the Randles-Sevcik equation. Electrochemical testing via cyclic voltammetry demonstrates an impressive areal capacitance of 173.2 +/- 9.6 mF cm-2 at 10 mV s-1 with Dunn's method distinguishing capacitive from diffusive contributions. Furthermore, EIS measurements highlight lower solution resistance in screen-printed devices, emphasizing the advantages of optimized electrode morphology for efficient charge transport. This study establishes a scalable approach for high-performance flexible supercapacitors, paving the way for next-generation energy storage solutions.
Keywords: Carbon nanomaterials; Coating techniques; Flexible Supercapacitors; PANI composites; X-ray micro-tomography